DETERMINANTS OF INFLATION IN CASE OF PAKISTAN - KHAN, ARIF; CHAUDHARY, GUL ZEB (Bulletin of Business and Economics (BBE), 2020)
Inflation is not only rise in price level but it’s also much complex phenomenon. Bit inflation exist in a natural and it’s like greasing element that bring change in commerce and economy. Economy is badly effected due to the high inflation. Major determinants of economy must be explored in order to control inflation. Recent study aims to put some light on determinants of economic growth particularly in Pakistan using the time series data over the period of 1980-2016.Auto regressive Distributed Lag technique is followed for the empirical analysis. Empirical findings show the long and short run effect of each individual variable on inflation. Empirical results reveal that electricity production from oil resource and Agriculture prices has a positive and significant relationship with inflation while Broad money and real effective exchange rate has a significant but negative relationship with inflation. Results in short run reflect that real effective exchange rate and Govt. expenditure has a positive and significant impact on inflation.